THE EFFECTS OF MACROECONOMIC CONDITIONS ON LOAN PORTFOLIO CREDIT RISK AND BANKING SYSTEM INTEREST INCOME - Mileris, Ričardas (Ekonomika, 2012)
This article presents on analysis of macroeconomic conditions in the EU countries in relation loan portfolio to credit risk and banking system interest income. The changing economic environment of banks influences their risks and activity results, so it is important to find the macroeconomic indicators that can determine the changes in debtors’ credit risk and banks’ financial condition. The banking system performs very important functions in a country’s financial system, so for its stability it is important to be able to predict the financial results of the banking system in relation to changes in the economic environment. The new Basel III Agreement seeks to improve the financial sector’s resistance to the possible negative scenarios in the economy and motivates to develop the credit risk assessment models considering their dependence on business cycles. For this reason, the statistical dependence between the set of macroeconomic factors and the loan portfolio credit risk together with interest income were estimated in this research. A statistical classification and regression tree model was developed, which allows to predict the possible changes in the interest income of a country’s banks with the 82.7% accuracy.